A case report of a pregnant woman with Sturge-Weber syndrome. Issue 4 (April 2020) - Luo, Ying; Yang, Yang; Chen, Xiu
A 23-year-old pregnant woman presented with headache and paroxysmal spasm of the right limb. She was born with a port-wine birthmark around the left eye frame. Magnetic resonance imaging revealed evidence of atrophy, calcification and vascular malformation in the left cerebral hemisphere. She was diagnosed with Sturge-Weber syndrome. She gave birth to a child without a port-wine birthmark through a caesarean section and her headache eased without surgical intervention of the intracranial vessel hyperplasia. This case suggests that pregnant women with SWS can deliver safely.